Prophylactic or therapeutic administration of Holarrhena floribunda hydro ethanol extract suppresses complete Freund's adjuvant-induced arthritis in Sprague-Dawley rats - Stephen Antwi; Daniel Oduro-Mensah; Jerry Asiedu-Larbi; Ebenezer Oduro-Mensah; Olga Quasie; Clara Lewis; David Darko-Obiri; Augustine Ocloo; Laud Kenneth Okine (BMC, 2022)
Abstract Background A hydro ethanol extract of the stem bark of Holarrhena floribunda (HFE) has been shown to be effective in the management of acute inflammation. This study was to evaluate usefulness of the extract for the management of chronic inflammation in a murine model. Methods Arthritis was induced in Sprague-Dawley rats using Complete Freund's Adjuvant. Anti-arthritic effect of the extract was evaluated in prophylactic and therapeutic treatment models at doses of 50, 200 and 500 mg/kg. Parameters assessed included oedema, serology of inflammatory response, bone tissue histology and haematology. Data were analysed by ANOVA and Tukey's multiple comparisons post hoc test. Results HFE at 50-500 mg/kg dose-dependently [P ≥ 0.0354 (prophylactic) and P ≥ 0.0001 (therapeutic) inhibited swelling of the injected paw upon prophylactic [≤ 81.26% (P < 0.0001) or therapeutic [≤ 67.92% (P < 0.01) administration - and prevented spread of arthritis to the contralateral paw. The inflammation alleviation activity was further demonstrated by decrease in arthritis score, radiologic score and erythrocyte sedimentation rate. HFE at all doses significantly reduced serum interleukin (IL)-1α (P < 0.0197), and 500 mg/kg HFE reduced IL-6 (P = 0.0032). In contrast, serum concentrations of IL-10, protein kinase A and cyclic adenosine monophosphate were enhanced (P ≤ 0.0436). HFE consistently showed better prophylactic than therapeutic activity. Conclusion HFE strongly suppressed Complete Freund's Adjuvant-induced arthritis and modulated regulators of inflammation, including IL-1α, − 6 and − 10. Taken together, the data suggest that HFE has potential for use as an agent for modulation of the inflammatory response.